1989
DOI: 10.1063/1.101057
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Be doping of Ga0.47In0.53As by low-temperature molecular beam epitaxy

Abstract: Layers of Ga0.47In0.53As grown on InP by a beam epitaxy method have been doped with Be to p=5×1020 cm−3 by growth at substrate temperatures as low as 365 °C. The maximum doping level is strongly growth temperature dependent. Heterostructure bipolar transistors with base doping p=1×1020 cm−3, current gain β=54, and unity current gain cutoff frequency fT=140 GHz are illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…In the nonequilibrium case, raised doping concentrations 10 20 cm ÿ3 have been achieved by epitaxial methods in Si 1ÿx Ge x :B [1][2][3], GaAs:N [4], GaInAs:Be [5], GaAs:C [6], and C in diamond [7]. Even higher, still electrically active, doping concentrations of up to 10 22 cm ÿ3 have been achieved in localized layers by so called -doping [8][9][10].…”
mentioning
confidence: 99%
“…In the nonequilibrium case, raised doping concentrations 10 20 cm ÿ3 have been achieved by epitaxial methods in Si 1ÿx Ge x :B [1][2][3], GaAs:N [4], GaInAs:Be [5], GaAs:C [6], and C in diamond [7]. Even higher, still electrically active, doping concentrations of up to 10 22 cm ÿ3 have been achieved in localized layers by so called -doping [8][9][10].…”
mentioning
confidence: 99%
“…Substrate temperatures (T s ) were measured using a thermocouple inserted into an In-filled well in the back of the a͒ Electronic mail: hkuo@filss.com Mo block in a manner similar to that reported by Hamm et al The thermocouple was calibrated by observing the melting point 525°C of InSb. 14 All of the samples were grown on epiready InP ͑100͒ semi-insulating substrates with the growth temperature 470°C and the growth rates of 1 and 0.55 m/h for InGaAs and InP, respectively. The npn HBT structure consists of: a 5000 Å n ϩ -InP subcollector (1ϫ10 19 cm Ϫ3 ), an n Ϫ InGaAs ͑4000 Å͒ collector, a 700 Å carbon doped base (4 ϫ10 19 cm Ϫ3 ), a 1000 Å InP emitter layer (8ϫ10 17 cm Ϫ3 ), and a 1500 Å n ϩ -InGaAs emitter contact layer (1 ϫ10 19 cm Ϫ3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Beryllium ͑Be͒ is a widely used p-type dopant in ultrahigh vacuum systems like molecular beam epitaxy ͑MBE͒ and metalorganic MBE or chemical beam epitaxy ͑MOMBE/ CBE͒ due to its large sticking coefficient at usual growth temperatures. 1 Even though extremely high Be doping ͑Ͼ10 20 cm Ϫ3 ͒ has been achieved for InGaAs by several authors, [2][3][4] high Be doping in InP has shown to be difficult both due to the lower solid solubility of Be in InP 5 and to surface degradation. 6,7 We show here a study on the growth mechanisms leading eventually to the observed surface degradation using x-ray diffraction ͑XRD͒, atomic force microscopy ͑AFM͒, Auger and secondary ion mass spectrometry ͑SIMS͒.…”
mentioning
confidence: 99%
“…We can observe that for the lower T Be , the slope of the curve follows that of the Be vapor pressure. 2,8 At the highest T Be , however, a saturation in the electrical activation of the dopant is reached. The maximum carrier concentration ͑ϳ2ϫ10 18 cm Ϫ3 in our case͒ does not change for the growth temperatures considered here.…”
mentioning
confidence: 99%
See 1 more Smart Citation